Rancang Bangun Alat Voltage Loss Detector Pada Transformator Percabangan - Edy Saputra; Muhammad Diono; Wiwin Styorini; Cyntia Widiasari (Politeknik Caltex Riau, 2022)
Branching transformers are transformers located at the branching of the Medium Voltage (TM) network. The output from this transformer will be forwarded to the homes of the public/PLN customers. The loss of voltage in the branching transformer due to a disturbance in the electricity network cannot be known by PLN officers before receiving a report from the public, so the duration of the blackout is very long. This is certainly very detrimental to the community and PLN. Voltage Loss Detector is designed to detect loss/ready voltage on branching transformers. This tool uses a ZMPT101B voltage sensor to detect voltage, an Arduino uno microcontroller and a GSM SIM800L module to send messages. After testing, this tool successfully sends a message when the voltage is ready/loss. The voltage values read by the ZMPT101B sensor on the R, S and T phases are 223.36 volts, 222.02 volts and 220.18 volts, while the voltage using a multimeter measuring instrument is 223 volts, 222 volts and 220 volts. The highest time Delay in receiving messages in the room is 20 seconds. The highest time Delay in receiving messages outdoors is 15 seconds. The signal quality of the GSM SIM800L module will affect the Delay in receiving messages. With this tool, power outages in branching transformers will be immediately noticed by PLN officers for follow-up.